2022
DOI: 10.3390/cells12010143
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies against Calcitonin Gene-Related Peptide for Migraine Prophylaxis: A Systematic Review of Real-World Data

Abstract: Objective: To perform a systematic review of real-world outcomes for anti-CGRP-mAbs. Methods: Following the PRISMA guidelines, we searched PubMed for real-world data of erenumab, galcanezumab, fremanezumab, or eptinezumab in patients with migraines. Results: We identified 134 publications (89 retrospective), comprising 10 pharmaco-epidemiologic and 83 clinic-based studies, 38 case reports, and 3 other articles. None of the clinic-based studies provided follow-up data over more than one year in more than 200 pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 175 publications
2
18
0
Order By: Relevance
“…Regarding the clinical studies of CGRP, many data remain unavailable, including data on interictal M0, MA, CM, and central NP. Hopefully, more clinical studies will reveal the consequences of CGRP modulator administration to clarify its efficacy in those subtypes of pain disorders [ 222 , 223 , 224 , 225 , 226 ]. Different TRP ion channels play distinct roles in both migraine and NP [ 227 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the clinical studies of CGRP, many data remain unavailable, including data on interictal M0, MA, CM, and central NP. Hopefully, more clinical studies will reveal the consequences of CGRP modulator administration to clarify its efficacy in those subtypes of pain disorders [ 222 , 223 , 224 , 225 , 226 ]. Different TRP ion channels play distinct roles in both migraine and NP [ 227 ].…”
Section: Discussionmentioning
confidence: 99%
“…Without a doubt, anti-CGRP treatments demonstrate promising efficacy and tolerability in a significant number of patients in both clinical trials and realworld studies (116)(117)(118)(119)(120)(121)(122)(123)(124). Furthermore, comparisons with older oral preventive drugs in real-world studies have revealed favorable results, both in terms of efficacy and tolerability (125,126).…”
Section: Anti-cgrp Medication and Medication Underusementioning
confidence: 99%
“…The CGRP monoclonal antibodies and the gepants are generally well tolerated. In clinical trials, the most commonly reported adverse events with the CGRP monoclonal antibodies are constipation and injection site reactions 26 . With respect to relative tolerability, in a meta-analysis of 19 clinical trials of CGRP monoclonal antibodies and gepants, 8 atogepant 60 mg 2 times a day (this dose does not have regulatory approval; odds ratio [OR]: 2.22; 95% confidence interval [CI]: 1.26 to 3.91) and galcanezumab 240 mg (OR: 1.63; 95% CI: 1.33 to 2.00) were most likely to be associated with treatment-emergent adverse events.…”
Section: Cgrp-targeted Migraine Preventive Medicationsmentioning
confidence: 99%